Structural and magnetic properties of LaMnO3 nanoparticles with varying la concentration - Tiwari P.; Rath C. (My University, 2025)
We study the structural and magnetic properties of LaMnO3 with varying La concentration. Reitveld refinement of X-ray diffraction pattern suggests phase purity of polycrystalline samples with I 2/a space group The XPS study shows the oxygen vacancies creation in both the samples. The temperature dependent magnetization results shows that Curie temperature increase with La deficiency however magnetic moment decreases. The magnetic moment of LaMnO3 is higher than La deficient LaMnO3 due to more oxygen vacancy creation. The Magnetic field dependent magnetization shows the ferromagnetic nature of the systems. © 2017 Author(s).